Analisis Senyawa β-Karoten pada Buah Pepaya (Carica papaya L.) Asal Kabupaten Konawe Selatan, Provinsi Sulawesi Tenggara - Irman Idrus; Sabda Wahab; Andi Fitrah Nugraha; Syaiful Bachri (LP3M Universitas Muhammadiyah Kendari, 2021)
South Konawe District at Southeast Sulawesi Province is a producer of agriculture such as Papaya fruit ranging from 1168 quintals each year. Papaya fruit contains β-carotene which plays an important role in the formation of vitamin A in the body. This research was conducted to determine the β-carotene content of papaya fruit by using variables planting method, fruitage, and fruit condition. The mashed fruit was extracted using n-hexane: acetone: ethanol (2: 1: 1) v/v, then separated from polar and non-polar solutions. Qualitative analysis was carried out using the Carr-Price method and quantitative analysis or determination of β-carotene levels using the UV-Visible spectrophotometric method λ = 452.0 nm. The qualitative test results showed that the papaya fruit in the papaya fruit obtained by cultivation and growing wild with each variable half-ripe, ripe, and not fresh papaya identified the presence of β-carotene. The results of quantitative analysis of β-carotene levels in cultivated papaya fruit were 1.76 μL, half-ripe 1.32 μL, and cultivated young papaya 1.22 μL. In wild ripe papaya 1.75 μL, wild half-ripe papaya 1.3 μL and wild young papaya 1.21 μL. There is an effect of each test parameter starting from the parameters of planting method, fruitage, and fruit condition on β-carotene content in papaya fruit.